How Does Exposure to Violence Affect School Delay and Academic Motivation for Adolescents Living in Socioeconomically Disadvantaged Communities in South Africa? - Herrero Romero, Rocio (Journal of interpersonal violence, 2021)
To date, little is known about the effects of violence on the educational outcomes of adolescents in disadvantaged communities in South Africa. In response, self-report data were collected from a socioeconomically disadvantaged sample of 503 adolescents aged 10 to 18 participating in a child abuse prevention trial in the Eastern Cape. Adolescents were purposively selected in the trial. This study applies Latent Profile Analysis (LPA) to examine relationships between past-month exposure to violence, school delay, and academic motivation. About 93.8% of adolescents in the sample experienced poly-violence—exposure to at least two forms of violence in the past month. Results identified two distinct profiles in the socioeconomically disadvantaged sample: Profile 1, adolescents exposed to more frequent poly-violence, and Profile 2, adolescents exposed to less frequent poly-violence. Being exposed to more frequent poly-violence was associated with greater risk of school delay—based on age-appropriate grade in South Africa. However, being exposed to more frequent poly-violence was not associated with lower academic motivation—adolescents showed high rates of wanting to achieve. Our findings suggest that exposure to more frequent poly-violence increases risk of school delay among adolescents from disadvantaged communities, while not affecting their academic motivation. Thus, although adolescents maintained aspirations and goals to do well at school, exposure to high frequency of violence affected their capacity to fulfill these aims.